2014
DOI: 10.1038/mi.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

NLRC4 expression in intestinal epithelial cells mediates protection against an enteric pathogen

Abstract: The inflammasomes play an important role in connecting the detection of endogenous and microbial danger signals to caspase-1 activation and induction of protective immune responses. NLRC4 is a cytosolic NOD-like receptor (NLR) that can trigger inflammasome formation in response to bacterial flagellin, an immunodominant antigen in the intestine. To characterize the role of NLRC4 in bacterially-triggered intestinal inflammation, we used the murine pathogen Citrobacter rodentium, an extracellular, attaching/effac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 47 publications
5
126
0
1
Order By: Relevance
“…Bacterial stimulation of intestinal mononuclear phagocytes (iMP) revealed that the commensals Bacterioides fragilis, Enterococcus fecalis, and Lactobacillus plantarum do not induce NLRC4-dependent release of IL-1␤, whereas Salmonella and Pseudomonas are potent stimulators of this cytokine (27). Indeed, NLRC4 seems to be a specialized guardian of the intestinal mucosal barrier, since its expression is highly elevated in resting iMPs and epithelial crypts (27,83). Therefore, it is not surprising that NLRC4 was found to be protective against intestinal pathogens such as C. rodentium or S. Tm, as well as against experimental colitis models such as DSS and AOM/DSS-induced tumorigenesis (12,14,26,43,83).…”
Section: Nlrc4mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial stimulation of intestinal mononuclear phagocytes (iMP) revealed that the commensals Bacterioides fragilis, Enterococcus fecalis, and Lactobacillus plantarum do not induce NLRC4-dependent release of IL-1␤, whereas Salmonella and Pseudomonas are potent stimulators of this cytokine (27). Indeed, NLRC4 seems to be a specialized guardian of the intestinal mucosal barrier, since its expression is highly elevated in resting iMPs and epithelial crypts (27,83). Therefore, it is not surprising that NLRC4 was found to be protective against intestinal pathogens such as C. rodentium or S. Tm, as well as against experimental colitis models such as DSS and AOM/DSS-induced tumorigenesis (12,14,26,43,83).…”
Section: Nlrc4mentioning
confidence: 99%
“…Indeed, NLRC4 seems to be a specialized guardian of the intestinal mucosal barrier, since its expression is highly elevated in resting iMPs and epithelial crypts (27,83). Therefore, it is not surprising that NLRC4 was found to be protective against intestinal pathogens such as C. rodentium or S. Tm, as well as against experimental colitis models such as DSS and AOM/DSS-induced tumorigenesis (12,14,26,43,83). Most recently, NLRC4 was found to restrict S. Tm infections through its activation of pyroptosis and expulsion of infected intestinal epithelial cells in to the lumen (98).…”
Section: Nlrc4mentioning
confidence: 99%
“…Similar to S. typhimurium, C. rodentium infection results in NLRP3-and NLRC4-dependent inflammatory responses that limit bacterial burden and tissue pathology, which was proposed to be IL-18 dependent (Kayagaki et al 2011b;Gurung et al 2012b;Liu et al 2012a;Alipour et al 2013). Unlike for S. typhimurium, NLRP3 and NLRC4 were shown to sense C. rodentium in nonhematopoietic cells, most likely in intestinal epithelial cells Nordlander et al 2013;Song-Zhao et al 2013). This matches the localization of C. rodentium, which does not invade host cells and instead remains firmly attached to intestinal epithelial cells.…”
Section: Intestinementioning
confidence: 99%
“…The current observations whereby flagellin lacking NLRC4-mediated activity could induce higher antibody responses against flagellin than could WT FliC was consistent with previous observations using A/J MyD88 2/232 and NLRC4 KO mice. 50 We also observed that FliC-L3A (deficient in NLRC4-mediated activity) induced significantly higher antibody titers than did FliC after intranasal immunization (data not shown). In summary, we could conclude that abrogating the NLRC4-mediated activity of flagellin upregulated the TLR5-mediated adaptive immune responses against flagellin.…”
Section: Discussionmentioning
confidence: 55%